Biphasic effects of blue light irradiation on different drug-resistant bacterium and exploration of its mechanism - Mu, Yifei; Shen, Yilin; Gretz, Norbert; Bouschbacher, Marielle; Miethke, Thomas; Keese, Michael (Biomedicines, 2025)
Background: Antimicrobial resistance is a problem that threatens the entire world population. Blue light irradiation (BLI) is a novel technology with a bactericidal effect. However, it has only been employed in experimental and preclinical trials. Methods: We employed BLI on four kinds of bacteria (Staphylococcus aureus, Pseudomonas aeruginosa, Proteus mirabilis, Klebsiella pneumoniae, and Escherichia coli) and six kinds of artificial implants utilizing a BioLight LED lamp and MEDILIGHT at a 453 nm wavelength. Results: The results showed that the antibacterial effect of BLI enhanced with time and dosage. Irradiation of 165.6 J/cm2 corresponding to 120 min of constant mode irradiation, resulted in a significant reduction in the CFU for all four strains. Moreover, the cycling mode (30 s on/30 s off) of the MEDILIGHT prototype showed a more effective microbial effect compared to the constant mode using the BioLight LED lamp. Pseudomonas aeruginosa was the most sensitive strain to BLI, and Staphylococcus aureus showed relatively greater resistance to BLI. BLI showed different antibacterial effects on various types of implants, indicating that different physical properties of artificial implants were more likely to influence the bactericidal effect of BLI. Decreased ATP highlighted energy deprivation after BLI. Genechip analysis of Escherichia coli under constant mode and cycling mode of BLI revealed the downregulation of metabolism-related pathways, and most genes involved in the TCA cycle were downregulated. Conclusions: Our results showed that cycling mode BLI has great potential for use in future disinfection applications. We also proposed a new viewpoint that energy deprivation might be another possible mechanism underlying the antibacterial effect of BLI.
Gesehen am 23.06.2025